Task difficulty affects the predictive process indexed by visual mismatch negativity - Kimura, Motohiro; Takeda, Yuji (Frontiers in Human Neuroscience, 2013)
Visual mismatch negativity (MMN) is an event-related brain potential (ERP) component that is elicited by prediction-incongruent events in successive visual stimulation. Previous oddball studies have shown that visual MMN in response to task-irrelevant deviant stimuli is insensitive to the manipulation of task difficulty, which supports the notion that visual MMN reflects attention-independent predictive processes. In these studies, however, visual MMN was evaluated in deviant-minus-standard difference waves, which may lead to an underestimation of the effects of task difficulty due to the possible superposition of N1-difference reflecting refractory effects. In the present study, we investigated the effects of task difficulty on visual MMN, less contaminated by N1-difference. While the participant performed a size-change detection task regarding a continuously-presented central fixation circle, we presented oddball sequences consisting of deviant and standard bar stimuli with different orientations (9.1% and 90.9%) and equiprobable sequences consisting of 11 types of control bar stimuli with different orientations (9.1% each) at the surrounding visual fields. Task difficulty was manipulated by varying the magnitude of the size-change. We found that the peak latencies of visual MMN evaluated in the deviant-minus-control difference waves were delayed as a function of task difficulty. Therefore, in contrast to the previous understanding, the present findings support the notion that visual MMN is associated with attention-demanding predictive processes.